2019
DOI: 10.1002/acn3.717
|View full text |Cite
|
Sign up to set email alerts
|

A novel CPT1C variant causes pure hereditary spastic paraplegia with benign clinical course

Abstract: Hereditary spastic paraplegia 73 (SPG73) was currently identified in only one family with variant in the neuronal isoform of carnitine palmitoyl‐transferase 1C (CPT1C) gene. We described a new family, in which affected individuals exhibited pure hereditary spastic paraplegia with benign clinical course. Exome sequencing revealed a novel nonsense variant in the CPT1C gene. The level of CPT1C mutant transcript significantly decreased compared to that of wild‐type transcript, and can be recovered after cyclohexim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The energetic regulation of LE/Lys plus-end transport mediated by CPT1C seems to be of particular importance for corticospinal neurons, the ones with longer axons in the body, since individuals carrying the missense CPT1C R37C or the nonsense CPT1C Q76X mutations develop HSP (Hong et al, 2019; Rinaldi et al, 2015). Arg37 is predicted to establish an electrostatic interaction with Glu3, stabilizing the Nα state of CPT1C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energetic regulation of LE/Lys plus-end transport mediated by CPT1C seems to be of particular importance for corticospinal neurons, the ones with longer axons in the body, since individuals carrying the missense CPT1C R37C or the nonsense CPT1C Q76X mutations develop HSP (Hong et al, 2019; Rinaldi et al, 2015). Arg37 is predicted to establish an electrostatic interaction with Glu3, stabilizing the Nα state of CPT1C.…”
Section: Discussionmentioning
confidence: 99%
“…Cpt1c KO mice show motor function deficits, such as ataxia, dyscoordination, and muscle weakness (Carrasco et al, 2013), in addition to learning deficits (Carrasco et al, 2012) and impaired hypothalamic control of body energy homeostasis (Casals et al, 2016; Pozo et al, 2017; Rodríguez-Rodríguez et al, 2019). Interestingly, the unique two CPT1C mutations described in humans to date have been associated with hereditary spastic paraplegia (HSP) (Hong et al, 2019; Rinaldi et al, 2015). HSPs are a group of inherited neurological disorders characterized by slowly progressive weakness and spasticity of the muscles of the legs, caused by axonopathy of corticospinal motor neurons (Blackstone et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, CPT1C has been found to be critical for correct regulation of food intake and peripheral lipid metabolism in the hypothalamus ( Gao et al, 2011 , 2009 ; Ramírez et al, 2013 ; Pozo et al, 2017 ; Rodríguez-Rodríguez et al, 2019 ). In addition, its rich expression in the cerebral motor cortex and cerebellum makes it relevant in motor coordination and activity ( Carrasco et al, 2013 ), underscored by human CPT1C mutations being associated with hereditary spastic paraplegia ( Rinaldi et al, 2015 ; Hong et al, 2019 ). Finally, due to its abundance in the hippocampus and in the cerebral cortex, CPT1C also plays a pivotal role in cognition ( Carrasco et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the heterozygous and homozygous variant of this SNP were also found in 300 controls (3/300 vs. 1/300), respectively. In fact, a recent study by Hong et al found a novel heterozygous variant (c.226C>T) resulting in a premature stop (p.Q76X) in exon 3 of the CPT1C, with benign clinical course (34). Therefore, whether the rs150853576 variant might be one of the "minor offenders" to contribute to cumulative risk and the occurrence of pure HSP in this pedigree, needs further functional verification.…”
Section: Discussionmentioning
confidence: 85%